ANALISIS PERANAN ETIKA BISNIS ISLAM PADA BISNIS PROPERTI PERUMAHAN BERSUBSIDI DI KOTA LANGSA, ACEH - Muhammad Riza (Jurnal Samudra Ekonomika, 2019)
Ethics is related to good living habits, both to oneself and to a society or community group. This means that ethics is related to values, good ways of life, good rules of life, and all the habits that are shared and passed on from one person to another or from one generation to another. This habit is then revealed in a patterned behavior that continues to recur as a habit. Specifically in the application of business ethics in all business organization activities in general. The purpose of this study was to determine the level of application of Islamic business ethics in subsidized housing companies in Langsa City. This type of research is qualitative research that is descriptive qualitative. Retrieval of data using observation, interviews and documentation. Samples taken by researchers are developers (developers), and residents of each housing company housing, sampling techniques of this study using random sampling techniques. The results showed that PT Avina Group, and PT Fatih Gravindo Raya, had implemented five axioms well in accordance with those measured from four aspects namely legal, economic, religious and ethical, in building subsidized housing in the city of langsa. The other two companies have not fully implemented the five axioms of Islamic business ethics, as evidenced by PT Kana Barokah Karya, which still has shortcomings in processing the level of public complaints in the quality of services, such as access roads to the complex, which until now has not been fully hoarded and also at PT Mitra Laut Group, which ignores the company's obligations to workers' rights to the promised wages from the initial contract signing.